What is effective communication in breastfeeding care? Perspectives from Latina women - Deanna Nardella; Sofia I. Morales; Rafael Pérez-Escamilla; Genesis Vicente; Leslie Brown; Natasha Ray; Kathleen O’Connor Duffany; Elizabeth C. Rhodes (PLoS ONE, 2025)
Background Despite effective communication being critical to providing person-centered care, little is known of effective communication in breastfeeding care from the perspective of Latina women in the United States (U.S.) who experience breastfeeding inequities. Our study identifies (a) what constitutes effective communication and (b) which provider practices promote or hinder effective communication in the context of breastfeeding care delivered within the pregnancy, delivery, and postpartum periods to Latina women in the U.S. Methods We analyzed data from a community-engaged study that included semi-structured interviews in English or Spanish with Latina women from low-income households in Connecticut. Women were asked about communication experiences with healthcare providers during their breastfeeding care across the pregnancy, delivery, and postpartum periods. Reflexive thematic analysis was used to analyze the data and develop a framework depicting key themes. Results Of the 21 women interviewed, approximately half were 25–31 years of age (48%), were born outside of the U.S. (52%), and most had prior children (86%). We identified two themes of what constitutes effective communication in breastfeeding care to Latina women: personalized breadth and depth of breastfeeding information (theme 1) and bidirectional exchange of information with providers (theme 2). Provider use of open-ended questions that explored women’s breastfeeding experiences, goals, and challenges asked across the breastfeeding care continuum promoted effective communication. Conversely, providers who asked about breastfeeding at a single visit and/or used rushed, checklist-style questioning left women with unmet information needs and hindered effective communication. While some women preferred communication aligned with their cultural and language preferences, others appreciated providers who engaged with non-fluent Spanish, seen as a supportive gesture. Our “Framework for Effective Communication in Breastfeeding Care” illustrates our findings. Conclusion Our findings could inform provider and systems level efforts to promote more effective communication in breastfeeding care, ultimately enhancing care quality and person-centeredness.